Disclosure Laporan Keuangan Pemerintah: Seberapa Pentingkah? - Nasrudin, Edy; Andriano, Rian (Cakrawala Management Business Journal, 2024)
Disclosure is an integral part of financial reporting that act as the final step in the accounting process, namely the presentation of information in the form of a full set of financial statements. Disclosure serves as a medium to present financial and non-financial explanations that cannot be presented in financial statements. This study aims to understand the importance of disclosure in financial statements through a literature review based on agency, signaling and stakeholder theory. The findings of this study indicate that public sector reporting entities are agents that have been mandated with full disclosure obligations in state financial accountability. The existence of disclosure will overcome or minimize the occurrence of information asymmetry so that stakeholders can assess the extent to which the organization's performance and continue to support the government which is currently running well. Disclosure can also prevent findings from occurring, as well as a form of follow-up on findings so that they do not become a continuing finding.